Sytuacja kryzysowa w Banku Częstochowa SA (w jaki sposób analizować kryzys, by podjąć skuteczne działanie) - Bielawski, Piotr (Bank Crisis on The Example of The Bank Częstochowa SA (How to Analyze The Crisis to Undertake The Efficient Remedies), 2008)
The logic of behaviour and outline of scheme presented in the paper should show the way of thinking of a PR specialist working in a crisis situation. While working on solving the crisis and building mechanisms protecting the organization against such problems in the future, new elements will appear, which should be taken into consideration, continuously modifying primary assumptions. The analysis of the crisis was carried out on the example of the situation in the Bank Częstochowa S.A. which started at the end of 2000 (this crisis, in any case, has its root in previous mistakes and wrong decisions). (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 212-229